Extending the TIME concept: what have we learned in the past 10 years? - Leaper, D.; Schultz, G.; Carville, Keryln; Fletcher, J.; Swanson, T.; Drake, R. (Wiley-Blackwell Publishing Ltd, 2012)
The TIME acronym (tissue, infection/inflammation, moisture balance and edge of wound) was first developed morethan 10 years ago, by an international group of wound healing experts, to provide a framework for a structuredapproach to wound bed preparation; a basis for optimising the management of open chronic wounds healing bysecondary intention. However, it should be recognised that the TIME principles are only a part of the systematic andholistic evaluation of each patient at every wound assessment. This review, prepared by the International WoundInfection Institute, examines how new data and evidence generated in the intervening decade affects the originalconcepts of TIME, and how it is translated into current best practice. Four developments stand out: recognition ofthe importance of biofilms (and the need for a simple diagnostic), use of negative pressure wound therapy (NPWT),evolution of topical antiseptic therapy as dressings and for wound lavage (notably, silver and polyhexamethylenebiguanide) and expanded insight of the role of molecular biological processes in chronic wounds (with emergingdiagnostics and theranostics). Tissue: a major advance has been the recognition of the value of repetitive andmaintenance debridement and wound cleansing, both in time-honoured and novel methods (notably using NPWTand hydrosurgery). Infection/inflammation: clinical recognition of infection (and non infective causes of persistinginflammation) is critical. The concept of a bacterial continuum through contamination, colonisation and infectionis now widely accepted, together with the understanding of biofilm presence. There has been a return to topicalantiseptics to control bioburden in wounds, emphasised by the awareness of increasing antibiotic resistance.Moisture: the relevance of excessive or insufficient wound exudate and its molecular components has led to thedevelopment and use of a wide range of dressings to regulate moisture balance, and to protect peri-wound skin, andoptimise healing. Edge of wound: several treatment modalities are being investigated and introduced to improveepithelial advancement, which can be regarded as the clearest sign of wound healing. The TIME principle remainsrelevant 10 years on, with continuing important developments that incorporate new evidence for wound care.